Neonatal rebound hyperkalemia associated with ritodrine alone: a case report - Keita Osumi; Kenichi Suga; Masashi Suzue; Ryuji Nakagawa; Shoji Kagami (BMC, 2021)
Abstract Background Betamimetics have been used for tocolysis extensively in the past, and one of them, ritodrine is widely used in Japan. Various adverse events have been reported for this agent, including newborn hypoglycemia and hypokalemia, as well as maternal hypokalemia and rebound hyperkalemia; however, cases of neonatal rebound hyperkalemia are not described in the literature. Case presentation A male infant born at 36 weeks of gestation by cesarean section at a local maternity clinic suddenly entered cardiopulmonary arrest with ventricular tachycardia and fibrillation due to hyperkalemia (K+, 8.7 mmol/L). No monitoring, examination of blood electrolyte levels, or infusions had been performed prior to this event. Maternal infusion of ritodrine (maximum dose, 170 μg/min) had been performed for 7 weeks prior to cesarean section. After resuscitation combined with calcium gluconate, the infant died at 4 months old due to serious respiratory failure accompanied by acute lung injury following shock. No cause of hyperkalemia other than rebound hyperkalemia associated with ritodrine was identified. Conclusions This case report serves as a warning regarding the potential risk of neonatal rebound hyperkalemia in association with maternal long-term ritodrine administration.